Oxidative stress and histopathologic biomarkers of exposure to bisphenol-A in the freshwater fish, Ctenopharyngodon idella - Mehwish Faheem; Khalid Parvez Lone (Universidade de São Paulo, 2018)
ABSTRACT Bisphenol-A (BPA) belongs to the family of endocrine disrupting chemicals (EDCs) and it is used in the production of polycarbonate plastic and epoxy resins. The reproductive toxicity of BPA is well documented but it also exerts its toxic effects through multiple pathways especially by inducing a state of oxidative stress and causing damage to the vital organs. In the present study, histopathologic and oxidative damage caused by BPA in liver and kidneys of fresh water cyprinid, Ctenopharyngodon idella was evaluated. LC50 of BPA for Ctenopharyngodon idella was determined by probit regression analysis. Fish were exposed to a sublethal concentration of BPA i.e. 3.2 ppm (1/2 LC50) for 14 days. Histologic studies revealed that BPA caused degenerative changes in liver and kidneys and exposure of sublethal concentration of BPA caused oxidative damage in both organs. Lipid peroxidation significantly increased in liver and kidneys of treated group. Catalase activity and reduced glutathione content significantly decreased in the group exposed to BPA compared to control and glutathione-S-transferase activity increased significantly in both organs exposed to the sublethal concentration of BPA. From this study it is concluded that BPA caused toxic effects in fish species by changing oxidative balance and damaging the vital organs.